The serum arachidonic acid/eicosapentaenoic acid ratio in children with healthy weight and obesity - Sánchez Meza, Karmina; Tene Pérez, Carlos Enrique; Sánchez Ramírez, Carmen Alicia; Muñiz Valencia, Roberto; Del Toro Equihua, Mario (Archivos Latinoamericanos de Nutrición (ALAN), 2020)
The western diet is characterized by a high consumption of n-6 polyunsaturated fatty acids (PUFAs) and reduced n-3PUFAs, this phenomenon has been parallel to the increase in the prevalence of obesity. The studies that have analyzed the association between serum PUFAs and the influence on the development of adiposity in children is limited and the findings are controversial. The present study compared the ARA/EPA (arachidonic/eicosapentaenoic) PUFA ratio in children with healthy weight vs. obesity in a cross-sectional study. Thirty children were diagnosed with obesity and 32 children with healthy weight determined through the age-specific body mass index (BMI) Z score, according to the WHO. The variables included were weight, BMI, waist circumference (WC), and the serum ARA/EPA ratio. The Student’s t test and Pearson correlation were performed and statistical significance was set at a p <0.05. The project was approved by the local ethics committee of the hospital Instituto Mexicano del Seguro Social. The serum ARA/EPA ratio was significantly higher in children with obesity compared with healthy weight (9.0 vs 5.4; p = 0.012). A statistically significant difference was observed between healthy weight boys and obese boys (p=0.003). Furthermore, the ARA/EPA ratio correlated positively with weight (r=0.336; p=0.008), BMI (r=0.373; p=0.003), WC (r=0.319; p=0.012) and cardio-metabolic risk (r=0.302; p=0.017). When performing a multivariate regression analysis, we identified that BMI was the only variable that remained significant and predicted the ARA/EPA ratio. In conclusion, the serum ARA/EPA ratio differed significantly in relation to weight and was higher in the obese children. La dieta occidental se caracteriza por un alto consumo de ácidos grasos poliinsaturados n-6(AGPI) y AGPIn-3 reducidos, fenómeno que ha sido paralelo al aumento en la prevalencia de la obesidad. Los estudios que han analizado la asociación entre AGPN en suero y adiposidad en niños son limitados y con hallazgos inconsistentes. El presente estudio comparó la relación ARA/EPA (ácido araquidónico/eicosapentaenoico) AGPI en niños con peso normal vs. obesidad. Es un estudio transversal donde treinta niños fueron diagnosticados con obesidad y 32 niños con peso normal determinado mediante el puntaje z del IMC para la edad, de acuerdo a la OMS. Las variables incluidas fueron peso, IMC, circunferencia de cintura (CC) y la relación ARA/EPA en suero. Se realizó prueba de t de Student y correlación de Pearson, la significación estadística se estableció en p <0,05. El proyecto fue aprobado por el comité de ética local del Hospital del Instituto Mexicano del Seguro Social. La relación ARA/EPA en suero fue significativamente mayor en niños con obesidad en comparación con el peso normal (9,0 frente a 5,4; p = 0,012). Además, la relación ARA/EPA se correlacionó positivamente con el peso (r = 0.336; p = 0.008), IMC (r = 0.373; p = 0.003), CC (r = 0.319; p = 0.012). Al realizar un análisis de regresión multivariable, identificamos que el IMC fue la variable predictora que permaneció significativa. En conclusión, la relación de suero ARA/EPA fue significativamente mayor en los niños con obesidad.